Personal reemployment accounts: Simulations for planning implementation - Christopher J. O'Leary; Randall W. Eberts (W.E. Upjohn Institute for Employment Research, 2004)
The proposed Back to Work Incentive Act of 2003 recommended personal reemployment accounts (PRAs) that would provide each eligible unemployment insurance (UI) claimant with a special account of up to 3,000 to finance reemployment activities. Account funds could be used to purchase intensive, supportive, and job training services. Any funds remaining in the PRA could be paid as a cash bonus for reemployment within 13 weeks, or drawn as extended income maintenance for exhaustees of regular UI benefits. Personal reemployment account offers would be targeted to UI beneficiaries most likely to exhaust their UI entitlements using state Worker Profiling and Reemployment Services (WPRS) models. The draft legislation called for a budget of 3.6 billion for PRAs, with the money to be committed over a two-year period. This report provides a simulation analysis of questions relevant to implementation of PRAs by states. The analysis is done using data for the state of Georgia. Simulations rely on recent patterns of intensive, supportive, and training services use. Simulations for alternative rules setting the PRA amount and varying behavioral responses are examined. Like the legislative proposal, simulated PRA offers are targeted using WPRS models. The key question examined is, how many PRA offers can a state make given a fixed budget? Proposed and alternative rules for substate budget allocation are also examined. The framework presented in this paper allows the exploration of several behavioral responses to incentives created by the PRA.
Keywords: J65; J68; H43; 330; Arbeitslosenversicherung; Simulation; Georgia (Staat); USA; Berufliche Integration